ANALISIS TENTANG KETENTUAN PENERIMA SUAP DALAM TINDAK PIDANA KORUPSI: Analysis Of The Provisions On Bribery Receivers In Corruption Crimes - Nabila Putri Suhendri; Dian Adrian Daeng Tawang (Faculty of Law, Universitas Trisakti, 2026)
Corruption in Indonesia continues to occur systematically, including bribery involving state officials as recipients of bribes. The use of articles on bribery, particularly Article 5 paragraph 2 and Article 12 letter b, still causes legal uncertainty. The problem formulation in this study is: What are the provisions on recipients of bribes in criminal acts of corruption, particularly in Law Number 20 of 2001? A normative method was used in this study, which was descriptive in nature, using secondary data and primary data to support the secondary data. Data analysis was conducted qualitatively. The results of the discussion and conclusions of this study are to illustrate that Article 5 paragraph (2) and Article 12 letter b both regulate the acceptance of bribes, but have fundamental differences in the elements and characteristics of the offense. The difference lies mainly in the form of the offense, where Article 5 paragraph (2) requires intent, while Article 12 letter b uses reasonable suspicion or knowledge with a heavier criminal penalty. The similarity in the core of the offense and the difference in the elements of the offense have the potential to cause misinterpretation, so a careful understanding of each article is necessary.